TEMPONE reduces renal dysfunction and injury mediated by oxidative stress of the rat kidney - Patel, NSA (2015)
Here we investigate the effects of the stable, water-soluble nitroxyl radical, TEMPONE, on renal dysfunction and injury caused by ischemia/reperfusion (I/R) of the rat kidney in vivo. TEMPONE significantly improved both glomerular and tubular function (serum urea, creatinine, creatinine clearance, and fractional excretion of Na+) in a dose-dependent manner and significantly attenuated the reperfusion-injury associated with I/R (urinary N-acetyl-beta-D-glucosaminidase, aspartate aminotransferase, assessment of renal histology). TEMPONE also markedly reduced the immunohistochemical evidence of the formation of nitrotyrosine and poly(ADP-ribose), indicating reduction of nitrosative and oxidative stress, respectively. The latter was reflected in vitro, where TEMPONE significantly reduced cellular injury of primary cultures of rat renal proximal tubular (PT) cells caused by hydrogen peroxide in a dose-dependent manner. Importantly, in contrast to its in vivo metabolite TEMPOL (which also provided protective effects against renal I/R and oxidative stress of PT cells), TEMPONE reduced renal dysfunction and injury without causing a significant reduction in blood pressure upon administration. These results suggest, for the first time, that TEMPONE can reduce the renal dysfunction and injury caused by I/R and the injury caused to PT cells by oxidative stress without producing the adverse cardiovascular effects observed when using other nitroxyl radicals. (C) 2002 Elsevier Science Inc.